Credit Card Transaction Security Using Facial Recognition Technology - Dr. S. Gandhimathi,; Ms. J. Soundarya, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The most prevalent issue nowadays in the modern world is credit card fraud. This is due to the growth in internet transactions and e-commerce websites. When a credit card is stolen and used for unauthorized purposes, or when a fraudster uses the card's information for his own gain, credit card fraud happens. Because the credit card offers significant usage as a payment instrument, it is often used. As we all know, there are several opportunities for attackers or hackers to acquire sensitive data from online transactions. For both valid and invalid transactions, the information is processed and an acknowledgement is given to the bank. Facial detection and facial recognition technology employing the Haar Cascade algorithm will be used in a credit card transaction system. Attacks on several privacy concerns, such as credit cards, are the major issue that credit card users deal with. Typically, individuals experience this when their credit card is given to an unexpected party or misplaced. Therefore, we are developing a system that will lower the possibility of credit card fraud. The technology we're working on will compare the person's face in the photograph to the dataset for that user. A database will be kept for the purpose of authentication. If the photos line up, it signifies the user is real, and processing will be permitted; otherwise, the transaction will not be allowed.
Keywords: Credit Card Transaction; Haarcascade Algorithm; Product Information; Booking Process